The effect of nonreproductive groups on persistent sexually transmitted diseases - Daniel Maxin; Fabio Augusto Milner (Mathematical Biosciences and Engineering)
We describe several population models exposed to a mild life-long sexually transmitted disease, i.e. without significant increased mortality among infected individuals and providing no immunity/recovery. We then modify these models to include groups isolated from sexual contact and analyze their potential effect on the dynamics of the population. We are interested in how the isolated class may curb the growth of the infected group while keeping the healthy population at acceptable levels.